2018
DOI: 10.1186/s12916-017-1001-7
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant tuberculosis treatment adherence in migrants: a systematic review and meta-analysis

Abstract: BackgroundMultidrug-resistant tuberculosis (MDR-TB) is a growing concern in meeting global targets for TB control. In high-income low-TB-incidence countries, a disproportionate number of MDR-TB cases occur in migrant (foreign-born) populations, with concerns about low adherence rates in these patients compared to the host non-migrant population. Tackling MDR-TB in this context may, therefore, require unique approaches. We conducted a systematic review and meta-analysis to identify and synthesise data on MDR-TB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 48 publications
1
28
2
4
Order By: Relevance
“…17,18 Social risk factors, such as social deprivation, vulnerable housing, mental health concerns or other comorbidities, also contributed to medication nonadherence. 19 Taken together, the above studies indicate that different factors are related to medication nonadherence in different regions. Hence, identifying specific factors that contribute to medication nonadherence to PTB treatment in different settings is important to design appropriate interventions to improve adherence.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…17,18 Social risk factors, such as social deprivation, vulnerable housing, mental health concerns or other comorbidities, also contributed to medication nonadherence. 19 Taken together, the above studies indicate that different factors are related to medication nonadherence in different regions. Hence, identifying specific factors that contribute to medication nonadherence to PTB treatment in different settings is important to design appropriate interventions to improve adherence.…”
Section: Introductionmentioning
confidence: 82%
“…17 , 18 Social risk factors, such as social deprivation, vulnerable housing, mental health concerns or other comorbidities, also contributed to medication nonadherence. 19 …”
Section: Introductionmentioning
confidence: 99%
“…Migrants with TB often have lower treatment success rates than native-born individuals. 4851 Understanding the underlying reasons for this is critical and context-specific. Several studies have shown that, even at the subnational level, identifying and targeting factors associated with default or loss to follow-up can improve health systems responses to TB treatment provision in migrant populations.…”
Section: Operational and Implementation Research On The Patient Carementioning
confidence: 99%
“…Cross-transmission between migrants and Brazilians was confirmed, yet the contribution by migrants was not substantial. Nellums et al [ 18 ] conducted a systematic review and metanalyses of 15 selected studies reporting MDR-TB treatment outcomes for 258 migrants and 174 non-migrants in European countries. The estimated rate of adherence to MDR-TB treatment across all patients was 71% .…”
Section: Mdr-tb In Refugeesmentioning
confidence: 99%